Study on the Effect of Current Pulsing During Gas Tungsten Arc Welding of Ti – 6Al – 4V Alloy - Kumar A.; Mahto M.K.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
The effect of current pulsing during gas tungsten arc welding (GTAW) of titanium alloy Ti – 6Al – 4V on the structure and properties of the weld is studied. Beads on plate welds are prepared on 2-mm-thick Ti – 6Al – 4V sheets using continuous- and pulse-current GTAW(keeping the heat input the same in both conditions). When welding, an indigenously developed shielding setup is used for protection against atmospheric contamination without any external shielding. The weld characteristics are determined by visual inspection, metallographic analysis, and microhardness testing. It is established that the use of current pulsing during GTAW provides finer grains, deeper weld penetration, and increased hardness in the weld zone and in the HAZ. The weld bead has acceptable quality and a silver color on the top and root sides. © Springer Science+Business Media, LLC, part of Springer Nature 2024.